A cryptic new species of Indigo Snake (genus Drymarchon) from the Florida Platform of the United States - Krysko, Kenneth L.; Granatosky, Michael C.; Nuñez, Leroy P.; Smith, Daniel J. (Zootaxa, 2016)
Indigo Snakes (genus Drymarchon) occur from northern Argentina northward into to the United States, where they inhabit southern Texas and disjunct populations in Mississippi, Florida and Georgia. Based on allopatry and morphological differences Collins (1991) hypothesized that the two United States taxa—the Western Indigo Snake, D. melanurus erebennus (Cope, 1860), and the Eastern Indigo Snake, D. couperi (Holbrook, 1842)—deserved full species recognition. Building upon this hypothesis with molecular and morphological analyses we illustrate that D. couperi is split into two distinct lineages. Based on the General Lineage Concept of Species, we describe the lineage that occurs along the Gulf coast of Florida and Mississippi as a new species, Drymarchon kolpobasileus. The new species is distinguished from D. couperi by a suite of morphological features, including a shorter and shallower head, deeper and shorter 7th infralabial scales, and shorter temporal scales. Overall, the presence of a deep 7th infralabial scale provides the best univariate identifier of D. kolpobasileus sp. nov. This study illustrates the usefulness of using both morphological and genetic data in refining accurate descriptions of geographical distributions.